Mengukur Perkembangan Keterampilan Computational Thinking Siswa SMA Negeri 3 Medan Pada Materi Limit Fungsi Aljabar - Angel Claudia Situmeang; Chindy Eskana Nababan; Pretty Viorella Br Ginting; Rosliana Siregar (Journal Innovation In Education, 2024)
Computational Thinking skills are students' ability to use mathematical concepts to solve problems systematically using algorithms and programming. This research aims to measure the development of Computational Thinking skills of students at SMA N 3 Medan on algebraic function limits material. The research method used is survey research with data collection using tests and observations. The subjects of this research were class XI students from SMA N 3 Medan who were studying algebraic function limits. The research results show that there is significant development in students' Computational Thinking skills after studying the material. The implication of this research is the need for a learning approach that focuses more on developing Computational Thinking skills in mathematics learning in high school.